Self-compassion and flourishing in Chinese high-performance athletes: exploring the mediating roles of positive emotion, coping strategies, and resilience - Wang, N.; Lee, J.-H.; Cho, H. (International Journal of Sport and Exercise Psychology, 2025)
General self-compassion, which is a vital aspect of healthy self-attitude, has been extensively examined in sport over the past decade. However, limited research has explored how athletes` self-compassion relates to positive emotional experiences that are crucial for enhancing their well-being and optimal functioning in sport. To address this gap, this study investigated the association between athletes` self-compassion and flourishing, focusing on psychological pathways involving positive emotion, coping strategies, and resilience. We collected data from 351 high-performance Chinese athletes (56% men and 44% women; mean age = 20.70 years) through an online survey. Results revealed that self-compassion was positively associated with positive emotion and resilience, although its direct association with coping strategies was not statistically significant. Importantly, we identified several significant indirect pathways linking self-compassion to flourishing. Specifically, self-compassion was indirectly associated with flourishing through positive emotion and coping strategies, through positive emotion and resilience, and through the extended sequence involving positive emotion, coping strategies, and resilience. These findings underscore the complex pathways through which self-compassion is related to athletes` well-being in competitive sport contexts.